2021
DOI: 10.29408/jel.v7i2.3400
|View full text |Cite
|
Sign up to set email alerts
|

Desain Pembelajaran Refleksi dan Translasi Berkonteks Klenteng Sam Poo Kong Semarang

Abstract: Reflection and translation material are critical to be mastered by students in learning transformation material. However, reflection and translation material are still difficult for students to understand. Therefore, this study aims to develop a learning trajectory that will assist ninth-grade students of Junior High School in grasping the notion of reflection and translation in the context of the Sam Poo Kong Temple in Semarang. The research used the design research method, which consisted of three stages: th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…The application of the Tedhak Siten tradition context, especially involving confinement equipment, proved effective in helping students understand the properties and definition of dilation. This finding is consistent with research by (Lestari et al, 2021;Refugio, 2018), which highlights the important role of context in supporting student understanding. Research by (Sari et al, 2022) said context can arouse students' interest and enthusiasm for learning.…”
Section: Retrospective Analysissupporting
confidence: 92%
“…The application of the Tedhak Siten tradition context, especially involving confinement equipment, proved effective in helping students understand the properties and definition of dilation. This finding is consistent with research by (Lestari et al, 2021;Refugio, 2018), which highlights the important role of context in supporting student understanding. Research by (Sari et al, 2022) said context can arouse students' interest and enthusiasm for learning.…”
Section: Retrospective Analysissupporting
confidence: 92%
“…IRME, which has been going on since 2001, has five main characteristics (Widyawati et al, 2016), namely the use of context, models, student contributions, linkages, and interactivity, that can facilitate students in understanding the concepts well. The use of IRME in this study is drawn upon the results of previous studies, which revealed that IRME could increase students' motivation in learning (Nursyahidah et al, 2018;Fahrurozi et al, 2018;Hartono et al, 2021), improve students' understanding (Sari et al, 2015), ease students to understand concepts (Fitri & Prahmana, 2018;Lestari et al, 2021), direct students' understanding from the informal stage to the formal stage, and create meaningful learning (Hartono et al, 2021).…”
Section: Introductionmentioning
confidence: 98%
“…Learning design is the main factor in classroom learning activities (Putrawangsa, 2018). From the above problems, it is necessary to design mathematics learning related to daily life (Lestari et al, 2021) with an appropriate approach for learning mathematics that can generate students' motivation and understanding of the concepts. Wahidin & Sugiman (2014) revealed that one approach applied in learning mathematics is the Indonesian Realistic Mathematics Education (IRME).…”
Section: Introductionmentioning
confidence: 99%